A CREAM FORMULATION HERBA ETHANOL EXTRACT Peperomia pellucida AND ANTIBACTERIAL ACTIVITY OF Propionibacterium acnes - Hasan, Dzulasfi; Faradika Abdullah, A. Yayan; Agustina, Satri; Idrus, Irman (Universitas Islam Negeri Alauddin Makassar, 2023)
Peperomia pellucida (L). Kunth) contains chemical compounds that are useful in the world of health in the pharmaceutical field. This study aims to make and test the physical quality of Peperomia pellucida herbal extract cream and to test the inhibitory power of Peperomia pellucida herbal extract cream against Propionibacterium acnes. The research method used was a laboratory experiment by making Peperomia pellucida extract using a physicochemical method to obtain 70% ethanol extract, then cream preparations were made and varied in several concentrations, namely 1% w/v; 2% w/v; and 3% w/v, then physical stability was carried out including organoleptic tests, homogeneity, pH, spreadability and the final stage was the Propionibacterium acnes antibacterial test by observing and measuring the inhibition zones. The results of the physical quality test showed that Peperomia pellucida herbal cream was made before and after storage at 4°C and 40°C for 24 hours with a concentration of 1% w/v; 2% w/v; and 3% w/v, on organoleptic, homogeneity, pH, spreadability and irritation tests, which meet the requirements for physical quality according to SNI standards. The antibacterial test was carried out using the well method and the inhibition zone formed was measured using a shear rod. Nutrient Agar (NA) as a medium with an incubation period of 1 x 24 hours with a temperature of 37OC. The average inhibition zone measurement results for a 1% concentration is 10.9 mm, 2% concentration is 12.1 mm, a 3% concentration is 12.8 mm and negative control no no inhibition zone.